Riesgos laborales de la construcción civil y afectaciones de salud de los obreros de la Pontificia Universidad Católica del Ecuador. Diseño de un manual de prevención de riesgos. - Torres Vásquez, Arturo (2014)
The workers of the civil building of the PUCE, find exposed to different labour risks, that affect his health and inside in the deterioration of his quality of life, in the social, economic and your family, and reflect in processes of production and productivity of the Institution, to local and National level. The present scientific investigation, allowed to research the labour risks of the workers of the civil building of the PUCE, that cause injuries muscle esquelético. Know the acute or chronic injuries that affect to a population very productive, like consequence of the labour risks to which see exposed, Allowed to know his needs to project us to a proposal to diminish the injuries muscle esqueléticas. Define and characterize the risks of the work in the building drove us to know the situations of insecurity in which exert the workers, that have more obligations and exigencies that fulfill and cues right permanently are being offended by a fault of prevention in risks of the building and a felicitous care of the health of the same. The investigation, with approach qualitative, allowed to define the labour risks of the civil building and the injuries muscle esqueléthic of the workers of the PUCE from the ambient in where exert, through a study exploratory, with design no experimental, recollected the information from his dynamic reality and holistic. Supported in the documentary investigation, bibliographic, of field and query to experts to define the theoretical frame scientific and the instruments to use, realized the diagnostic with a study descriptive, transversal to 62 workers, the data recollected were analyzed and interpreted to arrive to conclusions and recommendations. The results found showed that the workers of the civil building of the PUCE, find permanently exposed to labour risks that affect his system muscle esquelético, and require of a manual of prevention of risks to diminish this problematic, strengthening his knowledge’s and motivating a change of attitude, front to the subjects treated.